1972
DOI: 10.1088/0022-3735/5/1/030
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of laser Doppler velocimeter signals: frequency measurement

Abstract: The statistical properties of laser Doppler velocimeter signals are derived and used to obtain the signal zero crossing statistics for steady flows and high scattering particle concentrations. The results are applied to a model of a zero crossing counter, and expressions for the power spectrum and autocorrelation of the output signal are given in terms of the input signal autocorrelation. The RMS value of the fluctuations in the zero crossing counter output is calculated as a function of the optical system ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…This kind of zero analysis was considered first by R. Adrian in Ref. 2 and later on by H.Mishina and T.Asakura in Ref. 3 .…”
Section: Zero Counting Based On Analysis Of Probability Density Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…This kind of zero analysis was considered first by R. Adrian in Ref. 2 and later on by H.Mishina and T.Asakura in Ref. 3 .…”
Section: Zero Counting Based On Analysis Of Probability Density Functionmentioning
confidence: 99%
“…Currently, three major techniques are employed for signal processing in Doppler velocimetry [1][2][3] : Doppler spectral shift measurement, which is most often used; correlation measurement and zero crossings measurement. In the present paper we do a comparative accuracy analysis of these three major techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments such as laser light near threshold (Jakeman et al, 1970b), motions of particles in turbulent fluids (Diporto et al, 1969;Bourke et al, 1970), and light scattering from small number of particles undergoing Brownian motions (Schaefer and Berne, 1972;Schaefer and Pusey, 1972;Adrian, 1972) follow non-Gaussian statistics. Schaefer and Berne (1972) showed that non-Gaussian concentration fluctuations arise at low concentrations because the particles in the scattering volume have a Poisson distribution.…”
Section: Dynamic Light Scatteringmentioning
confidence: 99%
“…We refer to g,(z) as the 'normalised' conditional zero density. (20gN (7) corresponds to the density g(r) defined in Adrian (1972). )…”
Section: R Z 2 ( T )mentioning
confidence: 99%